KEMAMPUAN NUMERASI LEVEL 3; SURVEI TERHADAP PESERTA DIDIK SEKOLAH DASAR DI KOTA KUPANG - Adam Bol Nifu Benu; Paulina Riwu Ga; Taty Rosiana Koroh; Hiwa Wonda; Rista Aprilia Devi; Vera Bulu (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2024)
Numeracy ability is one of the abilities that students need to have to be able to overcome problems related to mathematical logic. The results of the PISA survey stated that Indonesia is classified as a country with the numeracy ability of students that has not been maximized. Meanwhile, to be more specific, the numeracy ability of students in areas spread throughout Indonesia is not clearly known. This research method is quantitative research, with a survey type. The subjects in this study were 364 students from elementary schools spread across Kupang City. Data collection was carried out using test techniques with a total of 15 numeracy test questions. The collected data was analyzed using descriptive statistics so that the average and distribution of the frequency of numeracy skills of students in elementary schools in Kupang City was known based on the level of their levels. The results showed that as many as 157 students or 45.35% had numeracy skills at level 3, namely being able to choose and apply simple problem-solving strategies; 143 respondents or 41.33% have numeracy skills at level 2, namely being able to use formulas, carry out procedures or agreements in solving problems; and the remaining 46 respondents or 13.29% have numeracy skills in Level 1 is being able to identify information and complete routine procedures according to clear instructions for the situation